0

# What is the variable number for 0.6 equals 3t?

Updated: 12/16/2022

Wiki User

12y ago

We're not at all sure what you mean by "variable number".

If 0.6 = 3t, then t = 0.2 .

Wiki User

12y ago

Earn +20 pts
Q: What is the variable number for 0.6 equals 3t?
Submit
Still have questions?
Related questions

### What is 3t plus 11 equals 29?

3t+11 = 29 3t = 29-11 3t = 18 t = 6

s = 7, t = -3

### What is the answer to 3t - 15 equals -9?

3t - 15 = -9 3t - 15 (+15) = -9 (+15) 3t = 6 3t (/3) = 6 (/3) t = 2

### What does t equal in the eqation 5-3t equals 0.77?

5-3t = 0.77 -3t = 0.77-5 -3t = -4.23 t = 1.41

6,000 pounds.

Yes.

### What is the answer to 22 equals 4 plus 3t?

4+3t = 22 3t = 22-4 t = (22-4)/3 t = 6

### What is the answer for st plus 3t equals 6 solve for s?

S = 3 st + 3t = 6 st = 6 - 3t s = (6 - 3t)/t = 6/t - 3

### What is 17 equals 3t-4?

It is an equation. Taking it step by step: 17 = 3t - 4 17 + 4 = 3t 21 = 3t 7 = t So the value of t is 7.

### Solve for t in the equation 3t plus 7 equals 2t-5?

3t + 7 = 2t - 5 3t = 2t - 12 t = -12

17

### How do you solve one fifith times three t minus six equals t plus six tenths?

By writing it out so you get: (1/5)*3t-6=t+(6/10) multiply and divide: (1/5)*3t=3t/5 6/10=3/5 which gives you: 3t/5-6=t+(3/5) put the variables on one side and the non-variable numbers on the other by adding and subtracting: 3t/5-6=t+(3/5) -3t/5 -3t/5 -6=2t/5+3/5 -3/5 -3/5 -33/6=2t/5 now multiply by the denominator on the variable side and divide by the numerator on the variable side (except the variable itself): -33/6=2t/5 *5 *5 -165/6=2t /2 /2 -165/12=t Now, reduce: -165/12=-55/4=-13.75 So, t=-55/4 or t=-13.75